Association of magnesium consumption with type 2 diabetes and glucose metabolism: A systematic review and pooled study with trial sequential analysis. Issue 3 (11th December 2019) - Zhao, Binghao; Deng, Huan; Li, Bo; Chen, Lian; Zou, Fang; Hu, Lei; Wei, Yiping; Zhang, Wenxiong
Abstract: Prevention of type 2 diabetes (T2D) with diet or diet supplementation is challenging. This article aims to draw conclusive associations between magnesium intake and T2D incidence and evaluate the effect of magnesium supplementation on glucose metabolism. Databases were searched for related articles from inception to May 15, 2019. Prospective cohort studies investigating the relevant relationship as well as randomized controlled trials (RCTs) assessing the effect of magnesium supplementation were eligible. We conducted trial sequential analysis (TSA) to prove the sufficiency of the current evidence. Twenty‐six publications involving 35 cohorts were included in the analysis. Compared to the lowest magnesium intake, the highest level was associated with a 22% lower risk for T2D; the risk was reduced by 6% for each 100 mg increment in daily magnesium intake. Additional analysis of 26 RCTs (1168 participants) was performed, revealing that magnesium supplementation significantly reduced the fasting plasma glucose (FPG) level (SMD, −0.32 [95% CI, −0.59 to −0.05], 2‐hour oral glucose tolerance test (2‐h OGTT) result (SMD, −0.30 [−0.58 to −0.02]), fasting insulin level (SMD, −0.17 [−0.30 to −0.04]), homeostatic model assessment‐insulin resistance (HOMA‐IR) score (SMD, −0.41 [−0.71 to −0.11]), triglyceride (TG) level, systolic blood pressure (SBP) and diastolic blood pressure (DBP). TSA showed an inverse association, with most benefits of magnesium supplementation on glucose metabolism being stable. In conclusion, magnesium intake has an inverse dose‐response association with T2D incidence, and supplementation appears to be advisable in terms of glucose parameters in T2D/high‐risk individuals.